Effect of the carbon tetrachloride extract of Trigonella foenum graecum seeds on the glycogen content of liver in diabetic rats - S Zahedi-Asl; F Saharnaz; A Ghassemi; B Zaree (Institue of Medicinal Plants, ACECR, 2006)
Background & Aims: Diabetes is a common endocrine disorder. Although the most common conventional treatment for diabetes is insulin, the diet therapy approach has many advantages in developing countries. Among many herbs, reported to possess antidiabetic activity, Trigonella foenum graecum (fenugreek) is one of the best in terms of efficiency and safety. The effect of carbon tetrachloride extract of fenugreek on liver glycogen has not been investigated until now. This study was designed to investigate the effect of carbon tetrachloride fenugreek in extract comparison with insulin on liver glycogen. Materials and Methods: For this purpose we used 3 groups of rats, each containing 10 animals. Stereptozotocin was administered to induce diabetes. One group served as control group, receiving no treatment; in the 2nd group, NPH insulin was administered on 3 consecutive days. For the third group, carbon tetrachloride extract of fenugreek was administered orally for 3 days. Blood glucose was measured before and after intervention. Daily water intake and liver glycogen were assayed at the end of treatment. Results: The results showed that fenugreek extract, like insulin, caused a significant decrease in blood glucose and daily water intake (P<0.05). A significant increase in liver glycogen, compared with the untreated group, was seen in the insulin and extract treated groups (P<0.05). Conclusion: In conclusion, the results of this study confirm the benefits of the traditional use of fenugreek for diabetes treatment.